Identification, pathogenicity, and fungicide sensitivity of Eutiarosporella dactylidis associated with leaf blight on maize in China - Cheng Guo; Xiaojie Zhang; Baobao Wang; Zhihuan Yang; Jiping Li; Shengjun Xu; Chunming Wang; Zhijie Guo; Tianwang Zhou; Liu Hong; Xiaoming Wang; Canxing Duan (Journal of Integrative Agriculture, 2024)
Maize (Zea mays L.) is an economically vital grain crop that is cultivated worldwide. In 2011, a maize foliar disease was detected in Lingtai and Lintao counties in Gansu Province, China. The characteristic signs and symptoms of this disease include irregular chlorotic lesions on the tips and edges of infected leaves and black punctate fruiting bodies in dead leaf tissues. Given favourable environmental conditions, this disease spread to areas surrounding Gansu. In this study, infected leaves were collected from Gansu and Ningxia Hui Autonomous Region between 2018 and 2020 to identify the disease-causing pathogen. Based on morphological features, pathogenicity tests, and multi-locus phylogenetic analysis involving internal transcribed spacer (ITS), 18S small subunit rDNA (SSU), 28S large subunit rDNA (LSU), translation elongation factor 1-alpha (TEF), and β-tubulin (TUB) sequences, Eutiarosporella dactylidis was identified as the causative pathogen of this newly discovered leaf blight. Furthermore, an in vitro bioassay was conducted on representative strains using six fungicides, and both fludioxonil and carbendazim were found to significantly inhibit the mycelial growth of E. dactylidis. The results of this study provide a reference for the detection and management of Eutiarosporella leaf blight.